Examining age and gender effects in physical performance in young athletes aged 12-16 years - Yanci, J.; Cámara, J.; Vizcay, J. J.; Young, W. B. (International Journal of Sports Science & Coaching, 2016)
The aims of the present study were to determine anthropometric and physical characteristics according to age and gender of young athletes, and to quantify the relationships among these characteristics. Sixty-four young high-level runners were divided into two groups according to their age: U14=under 14 year`s athletes; U16=under 16 year`s athletes. The U16 group presented higher values of the sprint 15m (p<0.01, d=1.14) and modified agility test (p<0.01, d=0.66) than the U14 group. However, the boys group presented higher values in the 505 agility test (p<0.01, d=0.63), modified agility test (p<0.01, d=1.26), horizontal countermovement jump (p<0.05, d=0.56), vertical countermovement jump (p<0.01, d=0.61) and arm swim vertical countermovement jump (p<0.01, d=0.63) than the girls group. ABSTRACT FROM AUTHOR